(untitled) (Mongolian Journal of Arts and Culture, 2024)
This paper explains how the Mongolian national postal stamp is not only a tool of telecommunication according to international standards, but also an important and multifaceted symbol of national art and culture, state and social policy, and representative of the country’s history by analyzing the image of the national postal stamp named Soyombo. Moreover, the paper will examine the “Soyombo” stamp based on the visual appearance of the stamp, such as symbols, graphics, colors, and compositions by observing, comparing, and using techniques of semiotics and structured methodology. Finally, this paper will suggest how to properly classify the stamps by conducting research and analysis on the types of stamps of the Mongolian post office. “Соёмбо” маркийн дүрслэлийн асуудалд Хураангуй: Монгол шуудангийн марк нь дэлхий нийтийн жишгээр харилцаа холбооны хэрэгсэл болох төдийгүй үндэсний дүрслэх урлаг, соёл, төр нийгмийн бодлого, түүхэн цаг үеийг харуулсан олон талт илэрхийлэл мөн болохыг “Соёмбо” маркийн дүрслэл дээр үндэслэн өгүүлэх болно. Мөн Монгол шуудангийн маркийн төрөл зүйлийг судлан өөрсдийн саналыг дэвшүүлж, тэдгээрийн дотроос үндэсний хэмжээний хоёр дахь марк болох “Соёмбо” маркийг бэлгэдэл, график дүрслэл, өнгө, зохиомж зэрэг дүрслэх урлагийн бүтээл болох талаас нь ажиглалт, харьцуулалт, тэмдэг зүй-бүтэц зүйн аргаар судалгаа хийж санал дүгнэлтээ дэвшүүлнэ. Түлхүүр үгс: дүрслэх урлагийн бүтээл, бэлгэдэл тэмдэг, зохиомж, дизайн, элемент